Impact of Composition on Pore Structure Properties in Shale: Implications for Micro-/Mesopore Volume and Surface Area Prediction - Yuan, Yujie; Rezaee, Reza; Al-khdheeawi, Emad; Hu, S.Y.; Verrall, M.; Zou, Jie; Liu, K. (AMER CHEMICAL SOC, 2019)
Pore structure properties such as pore volume, surface area, and pore size distribution (PSD) are the key petrophysical parameters in shales that control storage capacity, hydraulic conductivity, and the gas adsorption in potential. The nature of pore volume, surface area, and PSD are largely dependent on shale composition, which is highly heterogeneous in different formations. However, the quantitative effects of the clay content and total organic carbon (TOC) content on micropore and mesopore structural properties have not been fully explored yet. Here, we quantified the impact of clay and TOC contents on micro-/mesopore volume, surface area, and PSD using three shale formations with large compositional variations. The results indicate that clay and TOC contents synchronically influence the shale micro-/mesopore structure properties, but they function in different pore size ranges. The micropores are predominantly contributed by organic matter pores. For the first time, we discover that the mesopores ranging between 2 and 17 nm are primarily controlled by clay mineral pores, and the pores larger than 17 nm contain both clay and organic matter pores. We further develop four new equations to predict micropore volume, mesopore volume, micropore surface area, and mesopore surface area as a function of clay and TOC contents on the basis of the data collected from the three different shale types. The statistical analysis shows that our developed correlations are capable of predicting the pore structure properties in our investigated formations with acceptable accuracy. The newly established equations provide insightful implications for the precise formation evaluation in downhole practices.